Dependent Data in Social Sciences Research - Forms, Issues, and Methods of Analysis - Stemmler, Mark; Wiedermann, Wolfgang; Huang, Francis (Springer Verlag, 2024)
All authors of this volume are leading experts in their field of applying or developing new statistical methods for dependent data scenarios. This second edition is again truly international, with authors from the US, Europe and Asia. The book consists of 29 chapters and seven sections. Therefore, the new second edition can be considered a compendium on the up-to-date and cutting edge methods in the field. The seven sections are: (1) growth curve modeling, continuous time modeling and dynamic modeling, (2) network analysis and causal structure learning, (3) multilevel analysis, (4) longitudinal and cross-sectional dependent categorical data analysis and discrete sequence analysis, (5) longitudinal modeling and estimation of missing data, (6) item-response-modeling for dependent data and (7) other methods for the analysis of dependent data.<br